DAMPAK PANDEMI COVID-19, EDUKASI PROTOKOL KESEHATAN SEBAGAI STRATEGI EKONOMI BERGERAK DAN MELEK TEKNOLOGI PADA PASAR SUBUH TRADISIONAL DESA KERTAK HANYAR 2 [PANDEMIC IMPACT OF COVID-19, EDUCATION OF HEALTH PROTOCOLS AS A MOBILE ECONOMIC STRATEGY AND TECHNOLOGICAL LITERATURE ON TRADITIONAL EARLY MORNING MARKETS OF KERTAK HANYAR VILLAGE 2] - Darini Kurniawati (Jurnal Sinergitas PKM & CSR, 2021)
The impact of the COVID-19 pandemic is deeply felt by the community, especially in socio-cultural and economic life. Based on the results of observations and interviews with traders, there has been a 60% decrease in sales at the Subuh Market, Kertak Hanyar 2 Village, Banjar Regency, South Kalimantan. The residents of the dawn market have known about the COVID-19 pandemic through electronic media, but they still lack awareness in complying with the health protocol rules established by the government. Health protocol facilities are also not yet available. The dedication aims to improve the economy in the market at dawn but by adhering to health protocols to prevent the spread of COVID-19. This service was carried out together with the village head by disseminating health protocols and interviews with traders and buyers, providing masks and providing means of washing hands and soap. The result of the activity is the installation of health protocol education banners, traders using masks, the distance between traders is at least 1 meter and using hand washing facilities for buyers and traders at the market entrance. The socio-cultural and economic life of the people at Subuh Market are moving again with a sense of security.BAHASA INDONESIA ABSTRACT: Dampak pandemi COVID-19 sangat dirasakan oleh masyarakat, khususnya kehidupan sosial budaya dan ekonomi. Berdasarkan hasil observasi dan wawancara dengan pedagang, telah terjadi penurunan penjualan 60% di Pasar Subuh Desa Kertak Hanyar 2 Kabupaten Banjar Kalimantan Selatan. Warga pasar subuh telah mengetahui adanya pandemi COVID-19 ini melalui media elektronik, namun masih kurangnya kesadaran dalam mematuhi aturan protokol kesehatan yang ditetapkan pemerintah. Sarana protokol kesehatan juga belum tersedia. Pengabdian bertujuan untuk meningkatkan perekonomian di pasar subuh tetapi dengan mematuhi protokol kesehatan untuk mencegah penyebaran COVID-19. Pengabdian ini dilakukan bersama dengan kepala desa dengan melakukan sosialisasi protokol kesehatan dan wawancara kepada pedagang dan pembeli, pemberian masker dan penyediaan sarana alat cuci tangan dan sabun. Hasil dari kegiatan adalah terpasangnya spanduk edukasi protokol kesehatan, pedagang menggunakan masker, jarak antar pedagang minimal 1meter dan menggunakan sarana cuci tangan untuk pembeli dan pedagang pada pintu masuk pasar. Kehidupan sosial budaya serta perekonomian masyarakat di Pasar Subuh bergerak kembali dengan rasa aman.